2021
DOI: 10.3324/haematol.2021.279680
|View full text |Cite
|
Sign up to set email alerts
|

Elastic compression stockings for prevention of the post-thrombotic syndrome in patients with and without residual vein thrombosis and/or popliteal valve reflux

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Using predefined criteria, patients were classified as those who used proper stockings for at least 70% of daily time for at least one year after the thrombotic episode ('stockings' group), and those who did not ('no stockings' group). 27 The two groups were virtually comparable in terms of baseline characteristics, risk factors of venous thrombosis and risk factors of PTS. The findings were interesting.…”
Section: Elastic Compression Stockingsmentioning
confidence: 89%
See 1 more Smart Citation
“…Using predefined criteria, patients were classified as those who used proper stockings for at least 70% of daily time for at least one year after the thrombotic episode ('stockings' group), and those who did not ('no stockings' group). 27 The two groups were virtually comparable in terms of baseline characteristics, risk factors of venous thrombosis and risk factors of PTS. The findings were interesting.…”
Section: Elastic Compression Stockingsmentioning
confidence: 89%
“…Of the two vascular abnormalities, RVT was the one that impacted the study results most. 27 Accordingly, the ultrasound detection of RVT (especially if associated with PVR) three months after an acute proximal DVT has the potential to identify patients at a higher risk of developing PTS and of benefiting from ECS.…”
Section: Elastic Compression Stockingsmentioning
confidence: 99%
“…In the past 30 years, some large randomized clinical trials have shown that the main methods to prevent and treat AMI caused by venous thromboembolism include Catheter-directed thrombolysis and endovascular treatment ( 28 , 29 ), which can clear the disease to a certain extent, greatly reduce the burden of thrombosis, protect vascular and valve functions, and thus reduce the incidence of recurrence of myocardial infarction. However, in actual clinical applications ( 30 ), because there are very strict indications and contraindications for thrombolysis or endovascular therapy in patients with deep vein thrombosis (DVT), especially in patients with diabetes, while AE device therapy is non-invasive and convenient, a certain degree of compression can ameliorate limb pain and swelling in DVT ideally, thus greatly improving the compliance of patients, which can allow treatment alongside daily activities as well.…”
Section: Discussionmentioning
confidence: 99%
“…Another extremely debated topic regards DVT and PTS, where doubtful evidence still exists on the utility, kind and duration of the compression device and regime [ 1 , 4 , 10 , 13 ]. In fact, after the controversial SOX trial [ 14 ], which questioned the usefulness of MCS at reducing the incidence of PTS following an acute DVT, a few well-conducted studies and one Cochrane review [ 15 , 16 , 17 ] have been published on this topic. Overall, they re-confirmed the value of compression garments to reduce PTS in limbs affected by DVT, but likely on an individualised basis.…”
Section: Phlebologymentioning
confidence: 99%